2020
DOI: 10.23917/forgeo.v34i2.10667
|View full text |Cite
|
Sign up to set email alerts
|

GIS-based Flood Susceptibility Mapping Using Overlay Method in Central Sulawesi

Abstract: Central Sulawesi is the largest province on the Sulawesi island with a dominant sloping topographic condition and has a variety of soil types, flow density, land use and rainfall that makes this region vulnerable to flooding. Flooding is a hydrometeorological disaster that will adversely affect aspects of human life such as social and economic activities in an area because it can cause environmental damage, casualties and disrupt economic activity. Because of its enormous impact, the purpose of this research s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Those areas based on BPBD (2021) are classified as an area that often frequent floods. Previous research in the same study showed that some areas with flat slopes potentially flood incidents (Hutauruk et al, 2020). When the rain comes and raindrops hit the land surface, the water will flow and look for lower areas.…”
Section: Slope Classificationmentioning
confidence: 81%
“…Those areas based on BPBD (2021) are classified as an area that often frequent floods. Previous research in the same study showed that some areas with flat slopes potentially flood incidents (Hutauruk et al, 2020). When the rain comes and raindrops hit the land surface, the water will flow and look for lower areas.…”
Section: Slope Classificationmentioning
confidence: 81%
“…Furthermore, for light erosion, it is possible to conduct soil conservation measures mechanically, vegetatively and biologically, with limited use of chemical fertilizers, which tend to damage the land as they are unable to improve soil structure aggregation. The role of the government is also very important in helping to handle erosion so that it will not be a cause of flood disasters due to river shallowing (Hutauruk et al, 2020). In order to reduce the risk, mitigation must be made by understanding the signs of disaster due to mild or severe erosion (Shimizu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The elevation in the Wawar watershed is very diverse, the northern area of the Wawar watershed is the upstream area so it is higher than the southern area (downstream area). The nature of water always flows from higher to lower areas, so that areas that have lower elevations have a higher potential for flooding compared to areas that have higher elevations [13]. The majority of areas in the Wawar watershed are at an altitude of > 156 masl which is a mountainous area, the classification of altitude in the Wawar watershed can be seen in Figure 3 and Table 12.…”
Section: Data Used and Methodologymentioning
confidence: 99%